Talent management practices and employee retention among professional workers in five selected government linked companies in Malaysia / Zarina Begum Ebrahim ... [et al.] - Ebrahim, Zarina Begum; Abdul Razak, Nur Alia; Mustakim, Nurul Ain; Mokhtar, Noorzalyla; Sauid, Muna Kameelah (Universiti Teknologi MARA Cawangan Pahang, 2020)
In today's global business environment, talent becomes the potentially powerful source of competitive advantage. The talent management and employee retention has always been brought up by researchers, top management as well as HR Professionals to address its importance. Thus, the aims of this research are to examines the relationship between talent management practice and employee retention among professional workers in five Governmentlinked companies (GLC) in Malaysia. Five core talent management practices tested in this study were performance recruitment, performance management, succession planning, training and development and rewards and compensations. The population consists of 140 professional workers from five GLC companies. Data have been collected by questionnaire and analyzed using SPSS. The findings indicate all the five talent management practices have positive correlation on employee retention. Meanwhile, the result of multiple regressions shows only performance management and recruitment positively effect on employee retention. The limitations of the study include a small sample size, (N= 140) and was not longitudinal in nature and could be limited to generalizability to other samples. This study is significant for HR practitioners in setting the direction for future research in the area of talent management and help managers understand the significant roles of talent perception to design employee retention policies that are evidence based because the most potent action HR managers can take to ensure their strategic contribution is to develop a measurement system that convincingly showcases HR's impact on business performance. Future study also should incorporate a more strategic and holistic approach of investigation to include talent identification, talent development and talent management culture as important contributors to talent management competency.